2023
DOI: 10.1177/21582440221149727
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Consumer Environmental Ethics and the Willingness to Use Green Products

Abstract: Environmental ethics and moral obligation are action plan that helps to preserve the environment and has influenced consumption style. The utilization of green products and consumption has helped minimize environmental and health threats, which is considered to sustain the environment. In this study, we examine consumer environmental ethics, environmental attitude, social influence, and moral obligation through the mediation of the willingness to use green products toward green behavior. Using a questionnaire … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 114 publications
0
1
0
Order By: Relevance
“…Firstly, there are studies that have used structural equation modeling. For example, Alam et al [30] used SmartPLS3.0 to construct a model, and they found that consumers' environmental ethics, environmental attitudes, and ethical obligations had a positive effect on their willingness to use green products. The willingness to use green products also affected green behaviors and had a significant mediating effect, and the willingness to use green products mediated the relationship between consumers' environmental ethics, environmental attitudes, ethical obligations, and green behaviors at the same time.…”
Section: Research On Consumers' Willingness To Participate In Green A...mentioning
confidence: 99%
“…Firstly, there are studies that have used structural equation modeling. For example, Alam et al [30] used SmartPLS3.0 to construct a model, and they found that consumers' environmental ethics, environmental attitudes, and ethical obligations had a positive effect on their willingness to use green products. The willingness to use green products also affected green behaviors and had a significant mediating effect, and the willingness to use green products mediated the relationship between consumers' environmental ethics, environmental attitudes, ethical obligations, and green behaviors at the same time.…”
Section: Research On Consumers' Willingness To Participate In Green A...mentioning
confidence: 99%
“…The study aims to make a significant contribution to the existing knowledge by examining how TD can enhance organizational performance. The popularity of human resource management (HRM) practices, such as training and development, has led to increased investments in structured training programs across organizations worldwide (Alam et al, 2023;Hughes, Zajac, Woods, & Salas, 2020). However, the extent to which TD influences organizational performance is still unclear.…”
Section: Theoretical Implicationmentioning
confidence: 99%
“…These findings motivate consumers to pursue environmental protection, such as through green consumption. Alam et al (2023) suggest that environmental threats motivate the use and consumption of green products, encouraging the intention to use such products for environmentally friendly behavior. Besides, Büyükayman et al (2022) suggest that health and environmental awareness motivate consumers to choose and use green products that are beneficial for both health and the environment.…”
Section: Introductionmentioning
confidence: 99%